Testing for significant changes in popularity - Denny H. Meyer (South African Journal of Business Management, 1988)
A graphic procedure for determining whether a statistically significant change in television ratings has occurred is proposed. The method takes into account the fact that the ratings are generated from the same sample of viewers rather than from two independent samples. In addition it incorporates the effect of sample size. The method is applicable for the analysis of all market research data collected by such panel methods.
Keywords: 650